Transformasi Digital UMKM Shofi Cookies: Pengembangan Dashboard Penjualan Berbasis API, Database, dan Visualisasi Interaktif menggunakan wpDataTable - Sugiarto, Dedy; Sari, Syandra; Ariwibowo, Anung B.; Shofiati, Ratna; Gunawan, Muhamad Ichsan; Octavianus, M Arya (Yayasan Kajian Riset dan Pengembangan RADISI, 2024)
This community service activity aims to increase the efficiency and accuracy of sales data management at Shofi Cookies through the application of digital technology. The methods used include API-based dashboard development, database integration, and implementation of Custom CRUD Plugins and wpDataTables. The results show significant improvements in operational efficiency, ease of real-time data analysis, and data-driven decision-making capabilities. This program also provides training and mentoring to increase the capacity of human resources in utilizing technology optimally. It is hoped that the success of this activity can become a model for other SMEs in facing the challenges of digitalization in the era of digital transformation.